Hubungan Banten dan Lampung pada Abad XVII - Cahyani, Arini Gita; M, Syaiful; Perdana, Yusuf (FKIP UNIVERSITAS LAMPUNG, 2023)
The relationship between Banten and Lampung in the 17th century AD was motivated by several factors, such as the procurement of pepper commodities, securing trade routes in the Sunda Strait, and the development of pepper plantations. This study aims to analyze the relationship between Banten and Lampung, especially in politics and economics. The research method used in this study is the historical method because it examines events in the past. Historical research methods. consists of heuristic, criticism, interpretation, and historiography stages. In the heuristic stage, researchers try to collect historical sources, such as archives, books and journals. Next, the researcher investigates the authenticity of historical sources, both internally and externally. After examining historical sources, researchers will interpret the data obtained from historical sources in the interpretation stage. Finally, the author will present the results of the reconstruction of historical events through historical writing in the historiography stage. Then, the data analysis technique used in this study, namely historical data analysis techniques. The results of this study indicate that there was a relationship between Banten and Lampung in the 17th century AD in economic and political aspects. As a result, Banten is increasingly developing as a port city that promotes trading activities. The location of Lampung and Banten, which are connected to the Sunda Strait, further supports smooth relations between the two parties. In addition, the commodity of pepper produced in Lampung increased in the 17th century AD.